Answer:
y = 1
x = -2
Explanation:
1)Solve for x in the first equation, y=1/2x+2:
Subtract 2 from each side, y-2=1/2x
Multiply both sides by 2, 2(y-2)=x
Our first variable is now solved for, x=2(y-2)
2) Plug our second equation, y=-2x-3, into our solved variable:
x=2((-2x-3)-2) *we just replaced y with our second equation*
Simplify the equation, x=2(-2x-5) and then factor in the 2, x=-4x-10
Add 4x to both sides, 5x=-10
Divide both sides by 5
x=-2
3) Plug our x value into either equation (it give you the same result)
Equation 1)
y=1/2(-2)+2
y=-1+2
y=1
Equation 2)
y=(-2)(-2)-3
y=4-3
y=1
In the end you end up with x=-2, y=1!